Pemberdayaan Perempuan Melalui Program Kawasan Rumah Pangan Lestari (KRPL) Sebagai Upaya Peningkatan Potensi Sumber Pangan (Studi Pada Kelompok Wanita Tani di Kota Bandar Lampung) - Anita Pratiwi; Novita Tresiana; Ita Prihantika (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2020)
Food shortages is an issue that has imposes the community because it has to get food needs at a high price. To overcome the food shortages, every country needs to do the development potential food security to ensure the availability of sufficient, nutritious, and balanced food potential. The fulfillment of food can be done by utilizing the potential of existing land through the Sustainable Food House Area Program (KRPL). This study attempted to know groups of women farmers’ empowerment success through the Sustainable Food House Area Program and to know the supporting factors and inhibitory factors in the implementation of the Sustainable Food House Area Program.